Investigation into the formation processes of aluminium nitride in the plasma depending on the incidence angle of double laser pulses onto the target of D16T aluminium alloy in the air - Bazzal, Khoder; Fadaeian, Ahmad Reza; Zajogin, Anatolij P. (Journal of the Belarusian State University. Physics, 2017)
The influence of the incidence angle of double laser pulses on the desired formation of a component and charge composition of the surface laser plasma using the laser spark spectrometry method has been studied. The formation processes of aluminium nitride under the effect of focused double laser pulses incident at different angles on the surface of the target of D16T aluminium alloy in the air have been analyzed. It has been demonstrated that there is a possibility to increase both the numbers of aluminium ions with different charges in the surface laser plasma in the ablation mode and of AlN and AlO nanoclusters when a series of double pulses sequentially heat the target at the incidence angle about 75°. The conditions associated with the effects exerted by the laser parameters and by the processes on the target surface an within the plasma on the formation of the desired ionic and molecular compositions of the plasma due to double laser pulses have been considered.